Employment office. - United States. Army. Signal Corps (photographer):::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows employment office at the Portland Assembly Center. The Portland Assembly Center was formerly known as the North Portland International Livestock Exposition Center.